Genome-edited TaTFL1-5 mutation decreases tiller and spikelet numbers in common wheat - Sun, Jing; Bie, Xiao Min; Chu, Xiao Li; Wang, Ning; Zhang, Xian Sheng; Gao, Xin-Qi (Frontiers in Plant Science, 2023)
Tillering is a critical agronomic trait of wheat (Triticum aestivum L.) that determines the shoot architecture and affects grain yield. TERMINAL FLOWER 1 (TFL1), encoding a phosphatidylethanolamine-binding protein, is implicated in the transition to flowering and shoot architecture in plant development. However, the roles of TFL1 homologs is little known in wheat development. CRISPR/Cas9-mediated targeted mutagenesis was used in this study to generate a set of wheat (Fielder) mutants with single, double or triple-null tatfl1-5 alleles. The wheat tatfl1-5 mutations decreased the tiller number per plant in the vegetative growth stage and the effective tiller number per plant and spikelet number per spike at maturity in the field. RNA-seq analysis showed that the expression of the auxin signaling–related and cytokinin signaling–related genes was significantly changed in the axillary buds of tatfl1-5 mutant seedlings. The results suggested that wheat TaTFL1-5s were implicated in tiller regulation by auxin and cytokinin signaling.